ANALISIS NERACA AIR DI DAS LEMBUR KABUPATEN ALOR - Aydamel Takalapeta; Endeyani V. M; Thomas Lapenangga (Politeknik Pertanian Negeri Kupang, 2009)
Water Balance Analysis Of Lembur Watershed In Alor Regency. This Research was conducted in May - October 2007. The aim of this research is analyse the water balance of Lembur watersheed.Result of research showed : 1. Potency of Rainfall at Lembur watersheed conducted to farming system, however topography condition, drainage network density, vegetation, soil and land use less support the transfer function ofÂ watersheed; 2. Water balance of Lembur watersheed show deficit during 10 moon in one year. So that affect at produktvity of dry land farming Key word: water balance, watershed